Visual Function is Gradually Restored During Retina Regeneration in Adult Zebrafish - Hammer, Juliane; Röppenack, Paul; Yousuf, Sarah; Schnabel, Christian; Weber, Anke; Zöller, Daniela; Koch, Edmund; Hans, Stefan; Brand, Michael (Frontiers in Cell and Developmental Biology, 2022)
In comparison to mammals, zebrafish are able to regenerate many organs and tissues, including the central nervous system (CNS). Within the CNS-derived neural retina, light lesions result in a loss of photoreceptors and the subsequent activation of Müller glia, the retinal stem cells. Müller glia-derived progenitors differentiate and eventually restore the anatomical tissue architecture within four weeks. However, little is known about how light lesions impair vision functionally, as wells as how and to what extent visual function is restored during the course of regeneration, in particular in adult animals. Here, we applied quantitative behavioral assays to assess restoration of visual function during homeostasis and regeneration in adult zebrafish. We developed a novel vision-dependent social preference test, and show that vision is massively impaired early after lesion, but is restored to pre-lesion levels within 7 days after lesion. Furthermore, we employed a quantitative optokinetic response assay with different degrees of difficulty, similar to vision tests in humans. We found that vision for easy conditions with high contrast and low level of detail, as well as color vision, was restored around 7-10 days post lesion. Vision under more demanding conditions, with low contrast and high level of detail, was regained only later from 14 days post lesion onwards. Taken together, we conclude that vision based on contrast sensitivity, spatial resolution and the perception of colors is restored after light lesion in adult zebrafish in a gradual manner.